Integrasi Strategis Pendekatan Pemasaran Digital untuk Meningkatkan Pendapatan Iklan di Kardopa 99,4 FM : Studi tentang Navigasi Dinamika Media di Tengah Disrupsi Digital - Adelia Marwa Ujung; Muhammad Irwan Padli Nasution (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
Radio Kardopa 99.4 FM has become an integral part of the lives of the people of North Sumatra by presenting quality programs that combine entertainment and information. However, in the last five years, this radio has faced major challenges due to competition from digital platforms and changes in audience preferences. This research analyzes the marketing strategy implemented by Radio Kardopa to increase the number of advertisements and maintain its relevance in the market. The main strategies include promotion via social media, off-air activities, and personal selling approaches. Research results show that promotion via social media, such as TikTok and Instagram, helps increase visibility, but its effectiveness is not optimal. Off-air activities succeeded in strengthening relationships with local audiences, but were constrained by limited budgets. The personal selling approach remains effective in retaining loyal advertisers, but is less able to attract new advertisers. Fluctuations in the number of advertisements from 2017 to 2023 indicate the need for innovation and more consistent marketing strategies. Recommendations include developing creative content, investing in digital marketing technology, and collaborating with local MSMEs to expand the advertising market.